Role of Industry 4.0 in Pandemic Covid-19 and Shifting Business Models - Zobia Malik; Urooj Pasha (Journal of Management Practices, Humanities and Social Sciences, 2022)
We have conducted a brief literature review to learn more about the impact of Covid-19 on supply chains and how Industry 4.0 has helped to innovate business models as a result. Industry 4.0 (I4.0) was gaining popularity in every field before the pandemic. It brought a change in almost every area of life. It was becoming mandatory for organizations to change according to industry 4.0 parameters to remain competitive. Covid-19 has hit the world badly, leaving business operations to halt worldwide. It has accelerated the transformation process. It has forced practitioners to think about innovative Business models. Business models are the backbone of any progressive business that links its core technological functions and other activities to fulfil customers' needs. This paper sums up the transformation process under the umbrella of I4.0. It also summarises the effect of Covid-19 disruptions that hit the SC. It explores the stages which can be followed to recondition the business models. We summed up literature for practitioners to see possibilities to transform and survive existing disruptions. We have discussed emerging business models with the latest technologies. In this literature, we incorporate a four-step business model innovation process. Artificial intelligence, smart machinery, the Internet of Things, and Robotics are the main components of I4.0 that can revolutionize the value enhancement phenomena of any BM. Covid-19's effects on supply chain resilience and agility and the coping mechanisms provided by I4.0 were not thoroughly examined in previous studies.